Inductive-Deductive Reasoning in Qualitative Analysis using ATLAS.ti: Trending Cybersecurity Twitter Data Analytics - Mohamad A.M.; Yan F.Y.Y.; Aziz N.A.; Norhisham S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Application programs; Computer aided analysis; Social networking (online); ATLAS.; Cyber security; Data analytics; Deductive; Deductive reasoning; Inductive; Qualitative analysis; Qualitative data; Ti; Twitter; Data Analytics